On the estimation of a sensitive quantitative mean using blank cards. Issue 6 (19th March 2017) - Batool, Fatima; Shabbir, Javid; Hussain, Zawar
ABSTRACT: In this article, we introduce for the first time, the blank card methods for estimation of finite population mean of a sensitive variable. Two generic randomization devices are suggested, and for each device we identify the choices of special models. We introduce additive, multiplicative, and combination of both additive and multiplicative scrambling models that require use of a non sensitive variable. We derive the basic statistical properties of each model. It is interesting to note that various existing estimators can be viewed as the special cases of those presented here. The statistical efficiency of proposed techniques is compared with Greenberg et al. (1971 ) and modified Perri (2008 ) model. The proposed devices can easily be adjusted to achieve the required efficiency level by making suitable choices of different design parameters.